The Empathy Impact for Teacher’s Comprehension of the Child Personality in Perceptual Dimension - Dmytriyuk, Natalia (Psychological Prospects Journal, 2015)
The article deals with theoretical and empirical analysis of the empathy impact for teacher’s comprehension of preschooler personality in perceptual dimension. The nature of the categories «empathy», «comprehension», «social perception» are analyzed in the article. The important role of empathy in educator’s professional activity in the work with the children under school age, increasing the efficiency of communication has been defined and characterized.The scientific approaches to the problem comprehension (H. S. Kostyuk, M. V. Savchyn, I. D. Bekh) are considered. According to the analysis of existing scientific approaches to comprehension of a child’s personality includes the teacher’s development of social and perceptual components of pedagogical abilities. The conceptual vision of the process of comprehension as productive in teaching activities if it is based on the educator’s knowledge about feeling and comprehension of the partner’s inner world of the communication and especially in training and education are presented. The developed empathy – a key factor of success in pedagogical activities has been proved. Empathy is considered an important teacher’s quality.The features of educator’s empathy development are analyzed. Three levels of individual manifestation of teacher’s empathy are defined.The high level of empathy is characterized by a complete expression of the capacity for empathy to another person. Educators with high levels of empathy express such aspects of communication in relationships with children as a positive attitude, respect, sincerity, spontaneity and congruence.The average level educator’s empathy comprehension is characterized by the ability to recognize the mood, feeling responding adequately to the emotional health of the child. These teachers feel some difficulties adapting to the emotional world of pupils and do not always show positive attitudes to their perception.The low level of empathy appears in the inability of teachers to set empathic relationships with children, to show interest and recognize their thoughts and feelings.An empirical research proved that the most teachers demonstrate the average and low level of empathy development..